Joint association between tobacco smoke exposure and periodontitis and glycemic status - Hua, Xiaoguo; Li, Jiong; Hu, Rui; Zhang, Xiujun (Frontiers in Endocrinology, 2025)
ObjectiveBoth tobacco smoke exposure (TSE) and periodontitis were independently associated with glycemic status. However, studies focusing on the co-exposure and relative contributions of TSE and periodontitis to glycemic status are rare. This study intended to examine the joint and mutual associations between TSE and periodontitis and glycemic status among American adults.MethodsData were extracted from the National Health and Nutrition Examination Survey (NHANES, 2009-2014). Weighted logistic regression models were used to calculate their odds ratio (OR) and corresponding confidence interval (95% CI) with adjustments for confounding factors in the multivariate analysis that assessed the joint and mutual association between TSE and periodontitis and prediabetes and diabetes mellitus (DM).ResultsTSE and periodontitis were shown to be independently associated with prediabetes, and a positive association between periodontitis and DM was observed. Significant associations between both DM and prediabetes and the joint effect of periodontitis and TSE were detected. Moreover, a positive association between periodontitis and the risk of prediabetes and DM was observed in both active and passive smokers. Among the participants with TSE, a significantly higher risk of prediabetes or DM was found in those with moderate or severe periodontitis.ConclusionsTSE and periodontitis synergistically increased the risk of incident DM or prediabetes, and the deleterious effect of periodontitis on glycemic control could be reduced by smoking abstinence. The findings highlight the importance of avoiding constant exposure to tobacco smoke or quitting smoking for the management of the glycemic status of patients with moderate or severe periodontitis.